2015
DOI: 10.1111/jfpp.12590
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hard Red Spring Wheat Mill Stream Fractions Using Solvent Retention Capacity Test

Abstract: Quality and functionality of flour is dependent on chemical components, including protein, gluten, starch and arabinoxylans. The suitability of solvent retention capacity (SRC) for assessment of hard red spring (HRS) wheat quality was evaluated for mill stream flour samples. The HRS wheat sample was milled using a Buhler mill to produce six different flour streams. Flour samples were analyzed using AACC-I approved methods. The farinograph stability had very highly significant (P < 0.001) correlations with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 22 publications
4
18
0
Order By: Relevance
“…Data clearly indicated the distribution in wheat flour mill streams quality as expected and the average of all SRC values were found in the reduction flour streams. The SRCLa values are related to the amount of protein in a flour sample [1,8]. A more recent study observed that the SRCLa is related specifically to the glutenin content, not to the total protein content [23].…”
Section: Farinograph Extensograph and Solvent Retention Capacity mentioning
confidence: 99%
See 4 more Smart Citations
“…Data clearly indicated the distribution in wheat flour mill streams quality as expected and the average of all SRC values were found in the reduction flour streams. The SRCLa values are related to the amount of protein in a flour sample [1,8]. A more recent study observed that the SRCLa is related specifically to the glutenin content, not to the total protein content [23].…”
Section: Farinograph Extensograph and Solvent Retention Capacity mentioning
confidence: 99%
“…Flour for bread production typically requires considerable farinograph water absorption (FWA), high energy (E), and relatively high damaged starch and arabinoxylan contents. Flour for cookie production typically necessitates low FWA, minimal E and low damaged starch and arabinoxylan contents [8] Figures 2, and 3, showed that the break flour streams had the lowest values of SRCSo, SRCSu, SRCw, and GPI, while the last reduction flour streams had the highest values of SRCSu, SRCw and GPI. On the other hand, the highest SRCLa value was found in the fourth break stream, while the lowest estimates of SRCLa and SRCSo were found for the fifth break stream.…”
Section: Farinograph Extensograph and Solvent Retention Capacity mentioning
confidence: 99%
See 3 more Smart Citations